Correlation of Excess Body Weight and Socio-Physical Health Impact among Adolescents in Indonesia - Saifah, Andi; Munir, Muhammad Ardi; Parmin, Parmin; Hayati, Hayati; Rahman, Nurdin; Chaeriah, Siti (Poltekkes Kemenkes Palu, 2024)
The prevalence of overweight and obesity in adolescents is increasing in the world, predicted to rank 4th in the risk of obesity in Indonesia in 2030, high risk of adverse effects on the quality of life of adolescents in the form of metabolic disorders, physical discomfort, absenteeism from school, low achievement, and low self-esteem. The purpose of the study was to analyze the correlation between overweight and the impact of physical social health on adolescents. This study used a cross-sectional design. The study population was 242 adolescents with a sample size of 151 overweight adolescents from seven schools in Palu City. The research instruments were weight scales, height measuring microtoice, body mass index standards according to the Ministry of Health in 2020, tensimeter, blood sugar, cholesterol, uric acid, interview format related to physical complaints and self-esteem felt in the last three months, and academic and non-academic grades asked to the homeroom teacher. Data analysis was univariate and bivariate Pearson test and Spearman test. The results of the study were obese 21 (13.91%), overweight 130 (86.09%). Correlation test between overweight and cholesterol score (p=0.000; r=0.373), academic score (p=0.026; r= -0.18), self-esteem (p=0.004), systole blood pressure (p=0.53), diastole blood pressure (p=0.278), fasting blood sugar value (p=0.22), uric acid value (p=0.107), absenteeism (p=0.099), complaints (p=0.167). The study concluded that there was a positive correlation between overweight and high cholesterol levels, as well as adolescent self-esteem, while a negative correlation was found with academic grades. The research recommendation is to further analyze the behavior and sociocultural of overweight adolescents before nursing/health interventions.